Stiffness of the endplate boundary layer and endplate surface topography are associated with brittleness of human whole vertebral bodies - Nekkanty, Srikant (2010)
Stress magnitude and variability as estimated from large scale finite element (FE) analyses have been associated with compressive strength of human vertebral cancellous cores but these relationships have not been explored for whole vertebral bodies. In this study, the objectives were to investigate the relationship of FE-calculated stress distribution parameters with experimentally determined strength, stiffness, and displacement based ductility measures in human whole vertebral bodies, investigate the effect of endplate loading conditions on vertebral stiffness, strength, and ductility and test the hypothesis that endplate topography affects vertebral ductility and stress distributions. Eighteen vertebral bodies (T6-L3 levels; 4 female and 5 male cadavers, aged 40-98 years) were scanned using a flat panel CT system and followed with axial compression testing with Wood’s metal as filler material to maintain flat boundaries between load plates and specimens. FE models were constructed using reconstructed CT images and filler material was added digitally. Two different FE models with different filler material modulus simulating Wood’s metal and intervertebral disc (W-layer and D-layer models) were used. Element material modulus to cancellous bone was based on image gray value. Average, standard deviation, and coefficient of variation of von Mises stress in vertebral bone for W-layer and D-layer models and also the ratios of FE parameters from the two models (W/D) were calculated. Inferior and superior endplate surface topographical distribution parameters were calculated. Experimental stiffness, maximum load and work to fracture had the highest correlation with FE-calculated stiffness while experimental ductility measures had highest correlations with FE-calculated average von Mises stress and W-layer to D-layer stiffness ratio. Endplate topography of the vertebra was also associated with its structural ductility and the distribution parameter that best explained this association was kurtosis of inferior endplate topography. Our results indicate that endplate topography variations may provide insight into the mechanisms responsible for vertebral fractures.